Pengaruh Komunikasi, Kerjasama Tim dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Pengelola Limbah Kutai Kartanegara di Balikpapan - Megah Puspita; Dede Pebrianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the current era of globalization, the quality of human resources is a determinant for a country in facing increasingly competitive competition with the advancement of technological development and science has experienced rapid growth that has a significant impact on business progress and development. Human Resources (HR) are key in organizations and companies. For good management, companies need to have skilled and highly knowledgeable employees. This study aims to examine the influence of communication, teamwork and work environment on employee performance located at PT. Kutai Kartanegara Waste Management (PLKK) in Balikpapan. This research method uses quantitative research. Data collection technique using questionnaire with Likert scale. Sampling technique using nonprobability approach technique, namely purposive sampling is a sampling technique using certain criteria. With a population of 235 employees who will be sampled as many as 33 respondents with the criteria of employees at the company PT. Kutai Kartanegara Waste Management in balikpapan who have worked for at least 1 year. The analysis technique used in this study is to use the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, determination coefficient test (R2) Hypothesis testing, namely, t test, f test with prog tools. The results of this study indicate that the three independent variables, namely communication, teamwork and work environment have a significant effect both partially and simultaneously on employee performance. The R square value of the equation is 0.827, meaning that the dependent variable, namely employee performance, can be explained by the communication, teamwork and work environment (independent) variables in this study by 82.7%, while 17.3% is influenced by other variables not explained in this study.